Comparative Analysis of Creep Deformation in Ferritic Martensitic Steel Across BM, WJ, and HAZ Regions at 570°C - Ekaputra, I Made Wicaksana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
Creep is a time-dependent deformation in which failure can occur in years. The probabilistic assessment was a typical method for predicting creep deformation. The prediction was conducted by extrapolating the short-time creep laboratory test to the long-time data. A small deviation of extrapolation data was expected. Hence, a large number of creep tests were needed, since deviations in material properties cannot be avoided, especially in welded materials. In this study, the creep strain rate of Gr-91 steel was compared among the base metal (BM), weld joint (WJ), and heat-affected zone (HAZ). Welded steel was manufactured by the tungsten inert gas welding method. The creep test was conducted for each of the BM, WJ, and HAZ specimens using a lever-arm-type creep machine, following ASTM E139. The homologous creep temperature was set at 570 °C for a series of constant load ranges from 250 to 160 MPa. The strain-time curves of BM, WJ, and HAZ were generated after the specimens were fractured. The trend line of the creep strain rate is then determined using Norton’s equation. The creep mechanism of BM, WJ, and HAZ was investigated based on the creep exponent and strain hardening coefficient obtained from Norton’s equation.